Designing religious research studies : from passion to procedures - Woods, Charles Jeffrey, 1958- (Eugene, Oregon : Wipf & Stock Publishers, 2016)
Have you ever been frustrated with or perhaps even frightened about writing a religious research proposal? This book demythologizes the religious research design process by beginning with the writer's passion for ministry and then guiding the writer through a series of questions and exercises that lead toward a stress-free research proposal. The entire research process, including the description of context, literature review, data collection and presentation, and significance of the study are covered in this book. Through practical exercises, writers learn how to read research abstracts, choose between quantitative and qualitative methods, and identify themes and patterns in data. There is even a section that helps the writer transform an interesting study into an intriguing study! Students who have previously engaged this'funnel approach'to research design have found the process not only productive, but also enjoyable! This unique process of proposal development has been employed in various ecumenical as well as international contexts and works well in a wide variety of religious contexts including congregations, nonprofit agencies, hospitals, and educational institutions. If you want to learn to love data and write an appealing religious research proposal, this book is for you!
Introduction -- What is research? -- Passion -- Context -- Discovery and development -- Theological and theoretical background -- The research design -- Quantitative and qualitative -- Data collecting procedures -- Presenting the findings -- Significance of the study.
Includes bibliographical references.
Online resource; title from PDF title page (Proquest, viewed October 28, 2019).
Master record variable field(s) change: 050
Keywords: Religion -- Research -- Methodology; Research -- Methodology; RELIGION -- Comparative Religion; RELIGION -- Essays; RELIGION -- Reference; Research -- Methodology; Electronic books